Oil Droplets Transport Under a Deep‐Water Plunging Breaker: Impact of Droplet Inertia. Issue 12 (14th December 2018) - Cui, Fangda; Boufadel, Michel C.; Geng, Xiaolong; Gao, Feng; Zhao, Lin; King, Thomas; Lee, Kenneth
Abstract: Oil droplets transport in a deep‐water plunging breaker of height 0.18 m was simulated by coupling computational fluid dynamics with Lagrangian particle tracking. The Reynolds‐averaged Navier‐Stokes equations were solved in a two‐dimensional vertical slice within the computational fluid dynamics code Fluent to reproduce the movement of breaking waves in the absence of wind stress and large‐scale turbulence. The generated plunging breaker generated two additional (residual) breakers, consistent with experimental observations from the literature. The hydrodynamics of the breaker was subsequently used as input to the Lagrangian particle tracking code, NEMO3D, where the equation of motion was solved for each droplet by incorporating the major local forces including those due to the mass of the droplet. The droplet sizes were selected to vary from 100 to 600 μm. It was found that the droplet plume split into three clouds, one below and upstream of the first breaker, one below the second breaker, and one downstream of the third breaker. The largest penetration depth was within the second cloud. The largest entrainment (fraction of surface mass in the water column) occurred for the 100‐μm droplets, while the smallest entrainment occurred for the 600 μm. However, the 300 μm exhibited smaller entrainment than smaller droplets, which is due to the vortical nature of the breaker, which advected the 300 μm horizontally and then upward. This has implications on the biodegradation and dissolution of droplets of various sizes, and on the application of countermeasures such as dispersant. Plain Language Summary: Oil droplets transport in a deep‐water plunging breaker was simulated by coupling computational fluid dynamics with Lagrangian particle tracking. Based on the authors' knowledge, this is the first time to study the transport of oil droplets under an isolated breaker by coupling the computational fluid dynamics with Lagrangian particle tracking. Key Points: A deep‐water plunging breaker is reproduced with Reynold average Navier‐Stokes (RANS) approach Droplet transport was simulated while accounting for major forces (inertia, added mass, and lift) Accounting for droplet inertia results in larger droplets (300 microns), penetrating less than smaller droplets